FRI0488 Analysis of REAL Life Vasoactive Therapy in over 3000 Patients with Systemic Sclerosis (SSC) Reveals Considerable Undertreatment and Significant Changes of Treatment Practice since 2004. (10th June 2014) - Moinzadeh, P.; Elisabeth, A.; Blank, N.; Distler, J.; Fierlbeck, G.; Genth, E.; Guenther, C.; Hein, R.; Henes, J.; Hellmich, M.; Herrgott, I.; Koetter, I.; et al.
Abstract : Background: Vasculopathy is a major pathophysiological problem in patients with systemic sclerosis (SSc) and the main cause for Raynaud phenomenon (RP), digital ulcerations (DU), pulmonary arterial hypertension (PAH). It is not known, how SSc patients are treated with vasoactive agents in daily practice. Objectives: To determine, to which extent SSc patients are treated with vasoactive drugs. Methods: Data of 3248 patients of the registry of German Network for Systemic Scleroderma were analyzed. Results: Patients were treated with vasoactive drugs in 54.9% (1784) cases. Of these, 53% received calcium channel inhibitors (CCI), followed by 23.5% treated with intravenous Prostanoids (Iloprost, Prostavasin), 11.8% with beta-blockers, 11.3% with Pentoxifylline, 9.7% with Endothelin 1 receptor antagonists (ETRA), 4.6% with PDE5 inhibitors, 2.7% with topical vasodilative agents and 3.2% with others. Patients with RP received vasoactive therapy in 47, 4%, with DU in 66, 8% and with PAH in 71, 6% of cases. Logistic regression analysis revealed, that patients who suffered from PAH were significantly more often treated with PDE5 inhibitors (odds ratio (OR) 7.2; p<0.0001) and ETRA (OR 6.9; p<0.0001) and those with digital ulcers with ETRA (OR 2.8; p<0.0001) and intravenous prostanoids (OR 1.7; p<0.0001). Patients were more frequently treated with β-blockers, when they had arterial hypertension (OR 4.2; p<0.0001) and were male (OR 1.9; p<0.0001). In addition 25, 6% (830) patients were treated with ACE-inhibitors or AT1-receptor antagonists. They were often male and suffered from the diffuse form of SSc (p<0.001). Logistic regression analysis within this group clearly indicated that patients with hypertension (OR 4.9; p<0.0001) and renal insufficiency (OR 3.0; p<0.0001) were significantly more often treated with ACE inhibitors. When patients, registered after 2009, were compared to patients registered prior to 2004, it was found that after 2009 significantly more patients received ETRA (12% vs 5.5%; p<0.0001), beta-blockers (14.1% vs 7.6%; p<0.001), AT1R antagonists (12.5% vs 4.6%; p<0.0001), intravenous prostanoids (26.6% vs 18.2%; p<0.001) and ACE inhibitors (28.6% vs 23.1%; p<0.008). Conclusions: These data clearly indicate that many SSc patients with RP, DU, and PAH do not yet receive sufficient vasoactive therapy. Furthermore, in recent years a marked change of treatment regimens can be observed. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4946